Association between physiotherapist burnout and working environment during the coronavirus disease 2019 pandemic in Japan: A multicenter observational study. - Fumito Morisawa; Yuji Nishizaki; Yoshiki Irie; Shuko Nojiri; Takahiro Matsuo; Daiki Kobayashi; Hiroyuki Daida; Tohru Minamino; Tetsuya Takahashi (PLoS ONE, 2022)
Burnout among physiotherapists has been reported worldwide during the coronavirus disease 2019 (COVID-19) pandemic. However, no information was found on the prevalence of burnout among physiotherapists in Japan during the COVID-19 pandemic. Physiotherapists directly providing physiotherapy to patients with COVID-19 in the red zone of 487 medical facilities were evaluated for the prevalence of burnout using the Japanese version of the Maslach Burnout Inventory-General Survey (MBI-GS). The association between the presence or absence of burnout and the working environment was analyzed using logistic regression analysis. Among the 566 physiotherapists analyzed, 99 (17.5%) satisfied the MBI-GS criteria for burnout. Multivariate analysis showed that burnout was associated with the year of physiotherapy experiences [odds ratio (OR) 0.96, 95% confidence interval (CI) 0.93-0.99], feeling slight burden with infection control (OR 0.53, 95% CI 0.32-0.87), not feeling too burdened with infection control (OR 0.27, 95% CI 0.06-0.83), establishment of staffing standards for physiotherapy according to the number of beds (OR 1.80, 95% CI 1.09-2.96), and relaxation time (OR 0.49, 95% CI 0.30-0.82). Moreover, the OR increased as the self-improvement time decreased (OR 38.3, 95% CI 6.64-731). In Japan, the prevalence of burnout among physiotherapists during the COVID-19 pandemic was an intermediate value between the prevalence of burnout among physicians and nurses reported in previous studies. This study found the need to establish appropriate staffing standards for physiotherapy and support systems including secure self-improvement time and appropriate training according to physiotherapy experiences and each medical facility.